Genetic Profiling of the Plasmodium falciparum Population Using Antigenic Molecular Markers - Gupta, Purva (ScientificWorldJournal, 2014)
About 50% of malaria infections in India are attributed to Plasmodium falciparum but relatively little is known about the genetic structure of the parasite populations. The molecular genotyping of the parasite populations by merozoite surface protein (msp1 and msp2) and glutamate-rich protein (glurp) genes identifies the existing parasite population in the regions which help in understanding the molecular mechanisms involved in the parasite's drive for survival. This study reveals the genetic profile of the parasite population in selected regions across the country with varying degree of endemicity among them. We also report the prevalence of Pfcrt mutations in this parasite population to evaluate the pattern of drug resistance development in them.